Developmental and individual differences in the neural processing of dynamic expressions of pain and anger. - Manuela Missana; Maren Grigutsch; Tobias Grossmann (PLoS ONE)
We examined the processing of facial expressions of pain and anger in 8-month-old infants and adults by measuring event-related brain potentials (ERPs) and frontal EEG alpha asymmetry. The ERP results revealed that while adults showed a late positive potential (LPP) to emotional expressions that was enhanced to pain expressions, reflecting increased evaluation and emotional arousal to pain expressions, infants showed a negative component (Nc) to emotional expressions that was enhanced to angry expressions, reflecting increased allocation of attention to angry faces. Moreover, infants and adults showed opposite patterns in their frontal asymmetry responses to pain and anger, suggesting developmental differences in the motivational processes engendered by these facial expressions. These findings are discussed in the light of associated individual differences in infant temperament and adult dispositional empathy.